Dinamika Kewarganegaraan Ganda : Implikasi Hukum dan Kedaulatan Negara - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Annisa Yumaniar Nur Azizah; Kiran Ramadhani; Amaliya Ihsanti (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
The phenomenon of dual citizenship has become increasingly relevant in the context of globalization and high human mobility. This article examines the dynamics of dual citizenship from the perspectives of law and state sovereignty, which often give rise to challenges such as jurisdictional conflicts, double taxation, and uncertainty regarding individuals’ legal status. From the standpoint of sovereignty, dual citizenship presents dilemmas of loyalty, potential foreign intervention, and difficulties for the state in monitoring and protecting its citizens. This study employs a normative juridical approach supported by empirical data, analyzing statutory regulations and literature from books, journals, and relevant articles. The findings show that dual citizenship policies vary across countries, influenced by their respective national interests in terms of security, politics, and economics. In conclusion, to address the complexity of this phenomenon, dual citizenship policies should be designed to balance the protection of individual rights with national interests, supported by adaptive regulations that preserve legal stability and national sovereignty.